Practical multispectral lighting reproduction - LeGendre, Chloe; Yu, Xueming; Liu, Dai; Busch, Jay; Jones, Andrew; Pattanaik, Sumanta; Debevec, Paul (ACM transactions on graphics, 2016)
We present a practical framework for reproducing omnidirectional incident illumination conditions with complex spectra using a light stage with multispectral LED lights. For lighting acquisition, we augment standard RGB panoramic photography with one or more observations of a color chart with numerous reflectance spectra. We then solve for how to drive the multispectral light sources so that they best reproduce the appearance of the color charts in the original lighting. Even when solving for non-negative intensities, we show that accurate lighting reproduction is achievable using just four or six distinct LED spectra for a wide range of incident illumination spectra. A significant benefit of our approach is that it does not require the use of specialized equipment (other than the light stage) such as monochromators, spectroradiometers, or explicit knowledge of the LED power spectra, camera spectral response functions, or color chart reflectance spectra. We describe two simple devices for multispectral lighting capture, one for slow measurements of detailed angular spectral detail, and one for fast measurements with coarse angular detail. We validate the approach by realistically compositing real subjects into acquired lighting environments, showing accurate matches to how the subject would actually look within the environments, even for those including complex multispectral illumination. We also demonstrate dynamic lighting capture and playback using the technique.